Corporate philanthropic discourse - Raja Ahmad, Raja Adzrin (Curtin University, 2010)
This thesis derives important insights concerning the corporate philanthropic discourse of Australian listed firms. Corporate philanthropic discourse is analysed in two phases: (i) corporate philanthropic communication (Phase I) and (ii) corporate philanthropic involvement (Phase II). The first phase examines the noncommunication of corporate philanthropy. The second phase details the types and factors of corporate philanthropic involvement. In Phase I, a model on philanthropic communication is presented to better understand this (non-) communication and how such gift-giving is (or is not) communicated and in what form. In Phase II, the types and factors of corporate philanthropic involvement are examined. Data are gathered from over 1,500 annual reports and stand-alone sustainability reports for 2008.The findings of Phase I reveal that only 16.86 percent of Australian listed firms communicate any philanthropic information. This could be due to lack of clear reporting guidelines and absence of mandatory requirement for such disclosure. Further, it could also be argued that such muting is due to strategic reasons as communication opens the door for increased scrutiny. Yet more information dissemination, especially with better disclosure could enhance stakeholders’ confidence. Multivariate analyses indicate overwhelming evidence that firm size and profitability have a positive and statistically significant association with the extent of corporate philanthropic communication.Phase II focuses on corporate philanthropic involvement. Firms engage in various activities ranging from monetary to various types of non-monetary giving. Multiple regression results reveal that lagged free cash flow and firm size are statistically highly significant associated with corporate philanthropic involvement. These findings are consistent with slack resources theory tenets.Overall, the results from this thesis have implications for firms, regulators, investors, community and other interested parties. The key findings highlight over 80 percent (more than 1,200 Australian listed firms) choose to be completely silent on this key societal element. Given corporate philanthropy’s high prominence, the findings suggest that a more proactive effort to promote transparent and effective discourse is required with possible need for regulatory intervention.